Corticosterone and propranolol's role on taste recognition memory - Ruetti, Eliana Martha (2014)
Taste recognition is a robust procedure to study learning and memory processes, as well as the different stages involved in them, i.e. encoding, storage and recall. Considerable evidence indicates that adrenal hormones and the noradrenergic system play an important role in aversive and appetitive memory formation in rats and humans. The present experiments were designed to characterize the effects of immediate post training corticosterone (Experiment 1) and propranolol administration (Experiment 2 and 3) on taste recognition memory. Administration of a high dose of corticosterone (5 mg/kg, sc) impairs consolidation of taste memory, but the low and moderate doses (1 and 3 mg/kg, sc) didn´t affect it. On the other hand, immediate post-training administration of propranolol (1 and 2 mg/kg, ip) impaired taste recognition memory. These effects were timedependent since no effects were seen when drug administration was delayed 3 h after training. These findings support the importance of stress hormones and noradrenergic system on the modulation of taste memory consolidation.